Kebijakan Hukum Penutupan Lokalisasi Sunan Kuning dalam Penanggulangan Tindak Pidana Prostitusi Online Di Kota Semarang - Ook Mufrohim; Joko Setiyono (Universitas Serang Raya, 2020)
Prostitution is a social crime that occurs within the community. Argorejo localization or famous as Sunan Kuning is a prostitution localization located in Semarang City. The Mayor of Semarang, through his policy, closed the Sunan Kuning localization. This research shows that there are new problems due to the issuance of Criminal Law Policy related to the closure of the Sunan Kuning Prostitution Localization in Semarang City, but the policy has an impact on the proliferation of Online Prostitution in the City of Semarang which actually creates a very big danger because it can be accessed by everyone and including minors, only on the condition of having a smartphone. This research is useful for the government so that in an effort to deal with crime is going to be carried out in an integrated manner, so that the crime in eradication can really really be resolved at the root of the problem the crime arises. This research focuses more on criminal law policy in dealing with crime in an integrated manner. This research method is a Normative Juridical research method or a doctrinal research method, using a statutory and conceptual approach.